Errors committed by IELTS students in essay writing - Thapa, Kalpana (Chaitanya Research Journal, 2024)
International English Language Testing System (IELTS) is one of the widely accepted test designed to measure English proficiency of non-native speakers. It covers all four skills. The non-native speakers commit different errors as no one has got mastery over that language. Therefore, this article presents the errors committed by IELTS students in Essay Writing Task II in terms of grammar (article, and preposition) and mechanics. This study was based on primary and secondary sources of data. The sample population of the study consisted of eighty students studying in four purposively selected A, B, C and D consultancies of Banepa Municipality, Kavre. It was a survey research. The required data were collected by providing question of an opinion essay to the students. The students were taken mock test to collect the authentic data. The collected data were analyzed and interpreted statistically and descriptively. From the research, it was found that the total errors committed by the students were 611. The students committed 74 errors in article,62 errors in preposition and 475 errors in mechanics. It seems that the students made the highest number of errors in mechanics and lowest number of errors in preposition. It is apparent that the students were better in grammar and weak in mechanics.